2014
DOI: 10.1016/j.jamcollsurg.2014.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Is American College of Surgeons NSQIP Organ Space Infection a Surrogate for Pancreatic Fistula?

Abstract: Structured Abstract Background In the American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP) pancreatic fistula has not been monitored, although organ space infection (OSI) data are collected. Therefore, the purpose of this analysis was to determine the relationship between ACS NSQIP organ space infection and pancreatic fistulas. Study Design From 2007-11, 976 pancreatic resection patients were monitored via ACS NSQIP at our institution. From this database, 250 patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…are intimately related to SSI, particularly space/organ infections. Parikh et al reported that 55% of POPFs contributed to the occurrence of intra-abdominal abscess (26). In our data, SSIs were observed in 40% of patients with POPFs.…”
Section: Discussionsupporting
confidence: 62%
“…are intimately related to SSI, particularly space/organ infections. Parikh et al reported that 55% of POPFs contributed to the occurrence of intra-abdominal abscess (26). In our data, SSIs were observed in 40% of patients with POPFs.…”
Section: Discussionsupporting
confidence: 62%
“…Procedure-specific variables are required for ACS NSQIP to improve outcomes. (21, 26) Delayed gastric emptying, due to its frequency of occurrence and ability to affect immediate postoperative quality of life, cannot be ignored when discussing possible complications following PD.…”
Section: Discussionmentioning
confidence: 99%
“…We could not investigate certain clinically relevant complications, such as post-operative pancreatic fistula, or distinguish deep intra-abdominal collections versus superficial wound infections; this could result in potential under-estimation of pancreatic fistula rates when using post-operative infections as a surrogate. 31 There is also the possibility of miscoding or undercoding of information; randomized controlled trials at times demonstrate higher rates of complications following pancreatic surgery compared to retrospective studies. 32,33 Lack of patients' clinical picture with retrospective database work can result in an inability to determine the appropriateness of procedures.…”
Section: Revisitsmentioning
confidence: 99%